An infrastructure as a service integrity requirements: An interview study - Alabool, H.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Despite the Infrastructure as a Service (IaaS) cloud becomes increasingly important; several concerns prevent cloud users entry in the cloud; integrity is possibly one of the most relevant one. However, integrity of different IaaS cloud assets such as VM images, infrastructure applications and network configurations affected by many requirements (e.g., control areas and control criteria). This study aims to present results from an expert interview study to explore the new Integrity Control Areas (ICAs) and IaaS Integrity Control Criteria (ICC) that can influence the overall integrity degree within IaaS cloud. The analysis results brought out three ICAs and fifteen ICC which are associated with the main ICAs. Â© 2016 IEEE.